[Autokarikature] - Gliha, Oton; Kokotović, Dušan; Gecan, Vilko; Jovanović, Stanoje A.; Antunac, Grga; Šimunović, Frano; Tartaglia, Marino; Perić, Pavao; Crnobori, Josip; Mujadžić, Omer; Kljaković, Jozo (1939)
Autokarikature različitih autora. Glave.